Culinary Fusion In Transforming Traditional Recipes For Modern Tastes - Rahmat Kusnedi; Kezia Elsty; Muhammad Irfan; Lilik Hariyanto; Dikki Z. Choesrani; Aan Nurhasanah (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
In the culinary world, fusion cuisine is becoming increasingly popular, especially in terms of transforming traditional recipes to suit modern tastes. This concept includes the creation of innovative and appealing dishes by combining elements from various culinary traditions, both local and international. In the context of Indonesia, fusion food not only offers a variety of flavors but also introduces more appealing presentation styles that align with the preferences of the younger generation. Modification of traditional recipes such as soto, satay, and fried rice is a real example of culinary fusion. For example, Lamongan Soto, which is usually simple, can be transformed by adding seafood and salted eggs, giving it a richer flavor and a more luxurious appearance. Like fried rice, molecular gastronomy techniques can be used to create sambal in the form of pearl-like beads that are more visually appealing and flavorful. Fusion cuisine also attracts tourists. Chefs can expand the culinary market by adapting traditional Indonesian dishes into forms that are more palatable to international tastes, such as rendang burgers or sushi burgers. This increases interest in local cuisine and allows chefs to innovate and build a reputation worldwide. Although it offers many opportunities, implementing fusion cuisine has several challenges. When making modifications, maintaining the authenticity and identity of traditional food is a major challenge. Overall, culinary fusion provides a platform for innovation in the culinary world by combining tradition and modernity. This not only enriches the culinary experience but also allows chefs to conduct in-depth research on the characteristics of ingredients and cooking techniques from various cultures to ensure that the final result remains harmonious and delicious. This process involves repeated experimentation to achieve the ideal flavor combination without losing the essence of the original cuisine. Keywords: Culinary Fusion, Traditional Recipes, Food Innovation, Modern Taste, Gastronomy, Culinary Modification, Culinary Culture